The effectiveness of acupuncture for Parkinson's disease: An overview of systematic reviews. (May 2020) - Cao, Liujiao; Li, Xiuxia; Li, Meixuan; Yao, Liang; Hou, Liangying; Zhang, Weiyi; Wang, Yongfeng; Niu, Junqiang; Yang, Kehu
Highlights: We assessed the methodological quality of SRs/MAs with the AMSTAR 2 tool, and the GRADE approach to quantify the quality of evidence. We established strict inclusion criteria, used comprehensive search strategies to ensure that all relevant SRs/MAs were identified. We only included systematic reviews of randomized trials to reduce the risk of bias. Meta-analysis of acupuncture on patients with Parkinson's disease. Abstract: Objectives: Acupuncture is an alternative therapy for Parkinson's disease (PD), but its efficacy and safety are controversial. This overview aimed to summarize the existing evidence from systematic reviews (SRs) and meta-analyses (MAs) in order to assess the effectiveness of acupuncture as a treatment for PD. Methods: Seven electronic databases were searched from their inception until July 2019. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) and Assessment of Multiple Systematic Reviews 2 (AMSTAR2) checklists were used to assess evidence quality and methodological quality, respectively. The outcomes of study were calculated using mean differences (MDs) and risk ratios (RRs) with 95 % confidence intervals (CIs). A meta-analysis was performed using RevMan 5.3 software. Results: A total of 12 SRs/MAs were included. All 12 SRs/MAs had more than one critical weakness in AMSTAR 2 and were considered of critically low methodological quality. The quality of evidence was unsatisfactory according to the GRADE checklist. Meta-analyses showed that acupuncture combined with drug for the treatment of PD can significantly improve the total effectiveness rate compared with drug alone (RR = 1.25, 95 % CI 1.16–1.34, P  < 0.001). It was also found that acupuncture combined with drug significantly improved the UPDRS I–IV total summed scores (WMD=−6.18, 95 % CI -10.32 to –2.04, P < 0.001) and Webster scores (WMD=−4.20, 95 % CI -7.59 to –0.81, P < 0.001). Conclusion: Acupuncture might improve the UPDRS score, Webster score, and total effective rate in treatment of PD. It might be a safe and useful adjunctive treatment for patients with PD. However, we should interpret the findings of these reviews with caution, considering the overall limited methodological and reporting quality.